Rehabilitation of oncogynecological patients after antitumor therapy: ways of solution - A. V. Vlasina; L. E. Idrisova; A. G. Solopova; A. A. Koroleva; T. A. Blbulyan (IRBIS LLC, 2020)
The article provides a contemporary view on rehabilitation of oncogynecological patients. We considered physiological and psychological problems (surgical menopause and pain syndromes; impaired sexual function, distress, general intoxication, chronic fatigue associated with malignant neoplasm) occurring in women after antitumor treatment as well as outlined potential solutions. Not only traditional methods for correction of complications after antitumor treatment, but also opportunities for using alternative and adjuvant (supportive) therapy are presented. A special attention is paid to importance of relapse prevention during rehabilitation period. It is necessary to develop and introduce a multidisciplinary approach to this group of patients with the obligatory participation of physicians from different specialties - oncologists, obstetrician-gynecologists, rehabilitologists, psychiatrists, psychologists, etc.